2013
DOI: 10.1371/journal.pone.0084160
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Shallow RNA-Seq for Documenting Differential Gene Expression in Genes with High and Low Levels of Expression

Abstract: The sequencing depth necessary for documenting differential gene expression using RNA-Seq has been little explored outside of model systems. In particular, the depth required to analyze large-scale patterns of differential transcription factor expression is not known. The goal of the present study is to explore the effectiveness of shallow (relatively low read depth) RNA-Seq. We focus on two tissues in the honey bee: the sting gland and the digestive tract. The sting gland is an experimentally well-understood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Each pool was paired-end sequenced (2 × 100 nt) on a HiSeq. 2500 using a TruSeq SBS sequencing kit version 4, yielding ~12 million reads per sample, corresponding to at least 9.7 fold coverage (Supplementary Table S2 ), which is in the range of coverage reported in other honey bee transcriptome studies 24 , 25 , 122 . Sequence data was deposited into the NCBI Sequence Read Archive under accession number SRP101337 and is linked with NCBI BioProject #PRJNA377749.…”
Section: Methodsmentioning
confidence: 85%
“…Each pool was paired-end sequenced (2 × 100 nt) on a HiSeq. 2500 using a TruSeq SBS sequencing kit version 4, yielding ~12 million reads per sample, corresponding to at least 9.7 fold coverage (Supplementary Table S2 ), which is in the range of coverage reported in other honey bee transcriptome studies 24 , 25 , 122 . Sequence data was deposited into the NCBI Sequence Read Archive under accession number SRP101337 and is linked with NCBI BioProject #PRJNA377749.…”
Section: Methodsmentioning
confidence: 85%
“…Barcoding of samples permits pooling of multiple replicates allowing for the use of shallow-end sequencing to study a biological system. Due to the diminishment of the number of reads per sample, shallow-end sequencing can effectively be used to determine the fluctuations occurring in differentially expressed (DE) transcripts across a larger array of conditions than typically studied [ 29 , 30 ]. It has been suggested that analyzing the top 2500 transcripts can in fact cover over 80% of the biological information in an Arabidopsis transcriptomic project [ 30 ], and as little as 100,000 reads per samples are required for accurate prediction of mRNA fluctuations in human studies [ 31 ] suggesting that shallow-end RNAseq can provide substantial information.…”
Section: Resultsmentioning
confidence: 99%
“…the degree of their really expression. From the RPM values we obtained the individual expression levels of the enzyme sequences reacting to the treatments applied at a given time, that is, the degree of their expression [106].…”
Section: 𝐑𝐏𝐌 =mentioning
confidence: 99%